Environmental Neurochemistry and Neurodevelopmental Disorders in Pediatrics - Padmanabhan, Srihari; Tharan, Ojaswin (Journal for Research in Applied Sciences and Biotechnology, 2023)
Neurochemistry about environment and neurodevelopmental disorders in children is the interesting part of the analysis of the research paper. This paper focuses on the effects brought on by toxins in the environment such as heavy metals and pesticides to a developing brain and common disorder relating to ADHD as well as autism spectrum disorders. Placing the focus on policy and community intervention, as well as to determine the effective step for intervention, this study examines the biochemical pathways to neurotoxic exposures. Therefore, the aim of this current study is to enhance knowledge on risks to the environment in order to afford optimal neurodevelopment to children.